Retribution in the Wisdom Literature - Chandra Gunawan (Cipanas Theological Seminary, 2020)
Many scholars are reluctant to recognize the theological commonality among the wisdom literature. However, the concept retribution may connect the texts since it becomes their common question. Yet, their perspectives on retributive theology are diverse; in fact, they seem contradictory. This leads to the research question that I wish to address, i.e., how to understand the tension between these writing when they speak about the retribution. this essay will examine the concept of retribution in the OT, comprehend its meaning in the wisdom traditions, and compare it to other OT traditions.